Creativity and English Language Teaching From Inspiration to Implementation - Maley, Alan (Palgrave Macmillan UK, 2018)
This book offers a unique perspective on creativity in an educational environment where there is a relative dearth of literature on this subject. The authors link practice and principle to provide a practical and valuable guide for more creative language learning and teaching, using not only theoretical ideas but useful practical advice and recommendations on how better to introduce creativity into teaching and daily life. This innovative volume is sure to become a crucial reference point for teachers and practitioners of language teaching, and anyone interested in the ways in which creativity can be channelled into the teaching and learning process. Alan Maley has worked in the field of English Language Teaching for over 50 years. He has lived and worked in 10 countries, including India and China. He has published over 40 books in the field of language teaching. He is a Past-President of IATEFL and in 2012 received the ELTons Lifetime Achievement Award. His research interests lie primarily in creative writing and innovative materials development. Tamas Kiss is Associate Professor at Xi'an Jiaotong - Liverpool University, China. He has been involved with language teacher education programmes in Europe, the Middle East, South Asia, Latin America and South East Asia. His main interests include language teacher education, materials development, complexity science, language as a complex dynamic system and creativity.